1262 Case Series on the Use of Volume Assured Pressure Support (VAPS) in Patients with Interstitial Lung Disease and Progressive Hypercapnia. (27th May 2020) - LeMaster, William; Jun, Dale; De Cruz, Sharon; Zeidler, Michelle; Saggar, Rajan
Abstract: Introduction: Many patients with interstitial lung disease (ILD) experience progressive respiratory failure. While various therapies are implemented for acute hypercapnic respiratory failure during inpatient ILD flares, there is little data regarding the management of chronic hypercapnia in ILD with nocturnal Volume Assured Pressure Support (VAPS). We present three patients who were prescribed nocturnal VAPS for their progressive hypercapnia as a bridge to lung transplantation. Report of Case: Patient 1 is a 45-year-old woman with rheumatoid arthritis related ILD and progressive hypercapnia. Despite optimal therapy, her ILD resulted in an admission for hypercapnic and hypoxemic respiratory failure requiring treatment with BPAP, then transition to nocturnal VAPS on discharge. Dyspnea and pCO2 improved as an outpatient (Fig. 1). Patient 2 is a 70-year-old female with history of scleroderma associated ILD with severe PH and hypercapnia. Initiation of VAPS improved her pCO2 levels although she was readmitted after a few months of treatment for an ILD flare. Patient 3 is a 60-year-old patient with connective tissue disease related ILD who was admitted for respiratory failure due to pneumonia and was transitioned to BPAP for hypercapnic respiratory failure. Due to insurance issues she has been unable to obtain a home VAPS and her pCO2 remains elevated. A plot of each patient's pCO2 over time is in Figure 1. Conclusion: In patients with severe lung disease, the normal decrease in tidal volumes that occurs with sleep can result in CO2 retention. Non-invasive ventilation (NIV) is well-studied in both stable obstructive lung disease and exacerbations but there is little data examining the utility of NIV to treat the chronic hypercapnia of ILD. In this case series, nocturnal VAPS stabilized or reduced PCO2 in patients with ILD and hypercapnia. Additional studies are needed to assess long term effects of VAPS in these patients.